Analysis Of The Influence Of Training Effectiveness, Work Environment And Job Satisfaction On Employee Performance In The Tourism Industry - Merissa Fermica Iskandar; Ratnasari, Ani; Rika Nurhidayah; Dede Saparudin; Rifki Maulidani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to ascertain how employee performance is impacted by work environment, soft skill development, and job happiness. Researchers employed both qualitative and quantitative research techniques, as well as descriptive research, in this study. Permanent employees are the target population in this study. Nonprobability sampling strategies were employed by researchers. Next, judgment sampling a non-probability sampling method was employed in this study, with a sample size of 100 employees. Survey techniques are used in data collection. Under the survey research approach, questionnaires are distributed after in-depth interviews are completed by researchers. Multiple regression analyses have been used in this study. The study's findings indicate that training in soft skills and job satisfaction both positively and significantly affect employee performance. This implies that enhancing job satisfaction and developing soft skills in staff members can benefit their performance. However, the study's findings indicate that employee performance is not much impacted by the workplace. However, efforts to improve the work environment are still important to increase the overall well-being and satisfaction of employees, even though they do not directly affect their performance. As a recommendation, companies can pay more attention to and improve programs that can increase employee job satisfaction and soft skills training to support improving their performance.